Development of the Zebu herd of Bukedi Cattle at Serere, Uganda - Williams, E.; Bunge, V. A. (1952)
An account is given of the Serere Zebu herd form its foundation to the present time, together with the breeding policy that has been followed. Full records have been kept for this herd, which now numbers over 300 head, and from the figures available it has been shown that under the conditions described males reach maturity at about 66 months, and females at about 42 months, synchronizing with the age of first calving down. Figuers for the heaviest and lightest male and female calves are given, and figures based on the birth-weight of 320 calves show that it increase up to the third calf born, and then changes very little until the tenth calf. The percentage of effective calving has been 96.8, and amongst other matters described are the intervals between calvings, the effective life of cow, calf mortality, sex ratio, and carcass percentage for adult stock. The herd has been like-recorded since 1942 and the mean yield per cow has been increased from about 90 gals. In 1942 to 200 gals. In 1949. This is believed to be almost entirely due to better management. Three systems of calf management are compared. They show that calves kept on free range can compare with European breeds in putting live-weight; calves raised on free range for the first 7 months in their lives are on the average about 80 lb. Heavier at 3 years of age than those which are bucket-fed, or which suckle their dams although bucket-fed; and that suckled calves make nearly double the live-weight gains of the tree-range calves in there year of life.